2017
DOI: 10.1074/jbc.m117.796045
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar and spindle-associated protein 1 (NUSAP1) interacts with a SUMO E3 ligase complex during chromosome segregation

Abstract: The mitotic spindle is composed of dynamic microtubules and associated proteins that together direct chromosome movement during mitosis. The spindle plays a vital role in accurate chromosome segregation fidelity and is a therapeutic target in cancer. Nevertheless, the molecular mechanisms by which many spindle-associated proteins function remains unknown. The cleolar andpindle-ssociated rotein NUSAP1 is a microtubule-binding protein implicated in spindle stability and chromosome segregation. We show here that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…42 Previous studies have indicated that NUSAP1 contains an obvious SAP domain at its Nterminus. 15,33 This study demonstrated that ATR bound to the Cterminus of NUSAP1 (Fig. 4h-j).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…42 Previous studies have indicated that NUSAP1 contains an obvious SAP domain at its Nterminus. 15,33 This study demonstrated that ATR bound to the Cterminus of NUSAP1 (Fig. 4h-j).…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have demonstrated that NUSAP1 contains an SAP domain. 33 SAP domains are commonly found in many SUMO E3 ligases. SAP domains have also been implicated in substrate recognition and ligase activity.…”
Section: Nusap1 Knockdown Causes Dna Damage In Gbm Cellsmentioning
confidence: 99%
“…The under-expression of NUSAP1 seems to sensitize osteosarcoma cells to treatment with taxol, since NUSAP1 interacts with the SUMO E3 ligase complex contributing to adequate chromosomal segregation [45]. In oral squamous cell carcinoma, NUSAP1 knockdown has been observed to potentiate paclitaxelinduced apoptosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar and spindle associated protein 1(NUSAP1) is located in dynamic spindle microtubules at metaphase and anaphase of mitosis with a unique chromosomal central pattern. It interacts with SUMO E3 ligase complex in the process of chromosome separation near overlapping microtubules (44). NUSAP1 siRNA (L-004754-00) inhibited the drug resistance of human prostate cancer cells induced by NUSAP1, which suggested that NUSAP1 may be used as a biomarker of the antitumor activity of galiellalactone (45); however, to the best of our knowledge, there are currently few studies that focus on NUSAP1 in PAAD.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%